2003
DOI: 10.1007/s00521-003-0378-8
|View full text |Cite
|
Sign up to set email alerts
|

A neural network-based approach for calculating dissolved oxygen profiles in reservoirs

Abstract: A Neural Network (NN) modelling approach has been shown to be successful in calculating pseudo steady state time and space dependent Dissolved Oxygen (DO) concentrations in three separate reservoirs with different characteristics using limited number of input variables. The Levenberg-Marquardt algorithm was adopted during training. Pre-processing before training and post processing after simulation steps were the treatments applied to raw data and predictions respectively. Generalisation was improved and over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…For further assessment, the proposed models were compared with the results reported in the literature. Soyupak et al (2003) employed the ANN modelling approach to calculate the pseudo steady state time and space dependent DO concentrations in three different reservoirs, with entirely different properties. The correlation coefficients between neural network estimates and field measurements were higher than 0.95.…”
Section: Performance Of the Proposed Scenariosmentioning
confidence: 99%
“…For further assessment, the proposed models were compared with the results reported in the literature. Soyupak et al (2003) employed the ANN modelling approach to calculate the pseudo steady state time and space dependent DO concentrations in three different reservoirs, with entirely different properties. The correlation coefficients between neural network estimates and field measurements were higher than 0.95.…”
Section: Performance Of the Proposed Scenariosmentioning
confidence: 99%
“…Bateni et al (2007) have used ANNs and ANFIS models to estimate the equilibrium and time-dependent scour depth with numerous reliable database. ANNs have been used intensively in the development of a reservoir water quality simulation model (Soyupak et al 2003;Chaves and Kojiri 2007). Palani et al (2008) used an ANN model to predict and forecast temperature, salinity, DO and Chl-a in Singapore coastal.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction ability of ANFIS model is nearly similar to (Soyupak et al, 2003;Zhao, Nan, Cui, & Guo, 2007;Akpomie et al, 2016). Akpomie et al (2016) found a correlation coefficient of 0.86 for Cd concentration.…”
Section: Resultsmentioning
confidence: 57%
“…Several authors studied various AI techniques in environmental modelling, water quality monitoring and assessment, predicting the concentrations of heavy metals and other quality parameters, and estimation and forecasting in climatic sciences (Soyupak et al, 2003;Altunkaynak, Özger, & Çakmakcı, 2005;Kisi, 2005;Ocampo-Duque, Ferré-Huguet, Domingo, & Schuhmacher, 2006;Sengorur, Dogan, Koklu, & Samandar, 2006;Terzi, Keskin, & Taylan, 2006;Dahiya, Singh, Gaur, Garg, & Kushwaha, 2007;Icaga, 2007 2008; Hanbay, Turkoglu, & Demir, 2008;Dogan, Sengorur, & Koklu, 2009;Lermontov, Yokoyama, Lermontov, & Machado, 2009;Rehana & Mujumdar, 2009;Singh, Basant, Malik, & Jain, 2009;Ranković, Radulović, Radojević, Ostojić, & Čomić, 2010;Akkoyunlu, Altun, & Cigizoglu, 2011;Ay & Kisi, 2011Areerachakul, 2012;Hisar, Sönmez, Kaya, & Aras Hisar, 2012;Kisi & Ay, 2012;Qasaimeh et al, 2012;Sönmez, Hisar, & Yanık, 2012, 2013bSönmez, Hasiloglu, Hisar, Aras Mehan, & Kaya, 2013a;Chen & Liu, 2014;Emamgholizadeh, Kashi, Marofpoor, & Zalaghi, 2014;Heddam, 2014;Nemati, Naghipour, & Fazeli Fard, 2014;Yılmaz Öztürk, Akköz, Aşıkkutlu, & Gümüş, 2014;Ahmed & Shah, 2015;Alte & Sadgir, 2015;Csábrági, Molnár, Tanos, & Kovács, 2015, 2017...…”
Section: Introductionmentioning
confidence: 99%